Male Perpetrators of Intimate Partner Violence: A Comparison Between Incarcerated and Community Offenders - Cunha, Olga (International journal of offender therapy and comparative criminology, 2018)
The literature considers intimate partner violence (IPV) perpetrators to be a heterogeneous group. In Portugal, IPV perpetrators may be sentenced to either of two types of sentences: deprivation of freedom or alternatives to prison (in the community). In the present study, we performed a comparative analysis between 76 male individuals sentenced to prison and 76 male individuals sentenced to community measures for crimes against their current or former partners, using a set of psychological measures. The results indicate that although incarcerated and nonincarcerated IPV perpetrators demonstrate considerable differences, some similarities may also be observed. Incarcerated IPV perpetrators present the lowest socioeconomic status and education, perpetrate more severe IPV, and have more criminal convictions. A hierarchical regression analysis revealed that the use of weapons and objects increased the probability of IPV perpetrators belonging to the prison group above and beyond sociodemographic variables. Based on these results, implications for IPV perpetrators' treatment are discussed.